2010
DOI: 10.1002/jat.1535
|View full text |Cite
|
Sign up to set email alerts
|

Acrylonitrile induced apoptosis via oxidative stress in neuroblastoma SH‐SY5Y cell

Abstract: Acrylonitrile (ACN) is a chemical that is widely used in the production of plastics, acrylic fibers, synthetic rubbers and resins. It has been reported that ACN can cause oxidative stress, a condition which is well recognized as an apoptotic initiator; however, information regarding ACN-induced apoptosis is limited. This present study investigated whether ACN induces apoptosis in human neuroblastoma SH-SY5Y cells, and whether its apoptotic induction involves oxidative stress. The results showed that ACN caused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…ACN has been shown to cause oxidative stress in rat brain, neuronal cell lines, and primary glial cultures, with increased oxidative DNA damage and GSH depletion (Kamendulis et al, 1999a; Pu et al, 2006; Watcharasit et al, 2010). F 2 -isoprostanes are generated from the process of free-radical peroxidation of arachidonic acid (AA) and are long lived markers of oxidative stress (Milne et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…ACN has been shown to cause oxidative stress in rat brain, neuronal cell lines, and primary glial cultures, with increased oxidative DNA damage and GSH depletion (Kamendulis et al, 1999a; Pu et al, 2006; Watcharasit et al, 2010). F 2 -isoprostanes are generated from the process of free-radical peroxidation of arachidonic acid (AA) and are long lived markers of oxidative stress (Milne et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…1). ACN is cytotoxic in neuronal cell lines, causing an activation of Bax and induction of apoptosis (Watcharasit et al, 2010). Jacob and Ahmed found significant cell death in primary normal human astrocytes treated with 200 and 400 μM ACN, while Pu et al have observed 1 mM ACN to be a sublethal exposure in primary human astrocytes (Jacob and Ahmed, 2003; Pu et al, in preparation).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The M a n u s c r i p t 6 concentrations of antioxidants and AN (detailed below) were based on our pilot experiments. These concentrations were also selected based on the calculation by Chantara et al (2006) and Watcharasit et al (2010), which are relevant to human or animal exposures to AN (Major et al, 1998;Sweeney et al, 2003). Primary astrocytes at 80% confluence were treated with the three antioxidants according to the following protocols:…”
Section: Primary Cell Culture and Treatmentsmentioning
confidence: 99%